On computing some properties of Z and U(n) using C++ - Nor Haniza Sarmin, author; Shaharuddin Salleh, 1956-, author; Lim, Deborah Shin Fei, author; Universiti Teknologi Malaysia. Fakulti Sains Jabatan Matematik (Skudai : Universiti Teknologi Malaysia, 2006)
PSZJBL